2004
DOI: 10.1063/1.1779215
|View full text |Cite
|
Sign up to set email alerts
|

A discharge investigation of hydrogen and deuterium atom formation, and parahydrogen and orthodeuterium reconversion

Abstract: Hydrogen is flowed through a mild tesla-coil discharge and trapped at 3.8 K: New infrared absorptions of H2 are induced by interaction with trapped H atoms and H- anions. High purity parahydrogen and orthodeuterium samples are 1%-9% reconverted depending on the discharge pressure and recombination of atoms. Annealing the solid samples to 7 K reveals growth in p-H2 induced by o-H2, which shows that H atom recombination produces thermal nuclear spin populations. Similar results are found in discharge experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In the laser ablation process, H−H bonds are broken, and H atoms, H + , and electrons are produced. The H + is trapped in the argon lattice to give Ar n H + and Ar n D + at 903.6 and 643.1 cm -1 that have been assigned in early reports. , The H atom is attached to O 2 to give HO 2 radical (1388.4, 1101.9 cm -1 ) and D atom to O 2 to give DO 2 (1019.8 cm -1 ). , The O 3 , O 4 + , O 4 - , and O 6 - ions were also observed as common products as in laser-ablated metal atom reactions with O 2 . In the solid H 2 and D 2 experiments, H (D) and H - (D - ) are trapped in solid H 2 (D 2 ) to form clusters, which have been identified in previous papers. , …”
Section: Resultsmentioning
confidence: 78%
“…In the laser ablation process, H−H bonds are broken, and H atoms, H + , and electrons are produced. The H + is trapped in the argon lattice to give Ar n H + and Ar n D + at 903.6 and 643.1 cm -1 that have been assigned in early reports. , The H atom is attached to O 2 to give HO 2 radical (1388.4, 1101.9 cm -1 ) and D atom to O 2 to give DO 2 (1019.8 cm -1 ). , The O 3 , O 4 + , O 4 - , and O 6 - ions were also observed as common products as in laser-ablated metal atom reactions with O 2 . In the solid H 2 and D 2 experiments, H (D) and H - (D - ) are trapped in solid H 2 (D 2 ) to form clusters, which have been identified in previous papers. , …”
Section: Resultsmentioning
confidence: 78%
“…These researchers found H atom diffusion rates 100 times larger than the previous ESR measurements of H atom recombination and ascribed the difference to the intermolecular interactions of H + NO compared to H + H . Andrews and co-workers studied the induced IR transitions in solid hydrogen (and enriched pH 2 solids) produced by the presence of an H atom either by laser ablating metal atoms into the solids or by direct condensation of hydrogen gas subjected to tesla coil discharge in a quartz tube. , In these studies, H atom-induced peaks in pH 2 were identified at 4151.8 cm –1 , which show intensity half-lives compatible with the ESR measurements. More recently, Cao et al performed 193 nm photolysis studies on HCOOH/HBr mixtures in a Kr matrix aimed at studying the H + HCOOH reaction at low temperature .…”
Section: Introductionmentioning
confidence: 99%
“…This simply shows that the b-type transition reflects the total of satellite and monomer peaks, while for the a-type transition these two contributions are spectroscopically resolved and can be detected separately. If instead we make a correlation plot of the a-type sum (monomer plus satellites) versus the b-type transition intensity, then we observe a strong linear correlation with a fitted slope of 0.6489 (17). Indeed, this is what is expected based on the transitions strengths of a-type and b-type HDO ν 2 bend transitions, which show that the transition dipole has a larger projection along the inertial B axis [29].…”
Section: Shown Inmentioning
confidence: 69%
“…Fushitani and Momose used FTIR spectroscopy [15] to measure the H atom diffusion rate by studying the H + NO → HNO tunneling reaction after the in situ photolysis of NO in solid pH 2 at 5.2 K. In these studies the H atoms are produced as by-products of the NO photolysis, and the H-atom diffusion rate is determined from the growth in the IR absorption intensity of HNO. Andrews and co-workers studied the induced IR transitions in solid hydrogen (and enriched pH 2 solids) produced by the presence of an H atom either by laser ablating metal atoms into the solids or by direct condensation of hydrogen gas subjected to tesla coil discharge in a quartz tube [16,17]. In these studies H atom induced peaks in pH 2 were identified at 4151.8 cm -1 which show intensity half-lives compatible with the ESR measurements.…”
Section: Introductionmentioning
confidence: 75%